Soil inertia and shallow basement envelope impact on cellar internal temperature - Naima Sakami; Hassan Hamdi; Lahcen Boukhattem (Renewable Energy and Sustainable Development)
This work deals with a three dimensional numerical study of heat transfer by conduction between the soil and the shallow basement in the city of Marrakech (Morocco). The heat transfer equation is solved by the finite difference method using the implicit alternative direction (ADI). The internal temperature of the cellar is computed by using energy balance equation in the cellar. The objective of this work is to evaluate the effects of the nature of the soil, the nature of the walls, the thickness of the walls of the cellar and the distance L far from the cellar on the internal temperature and the heat exchanged between the soil and the shallow basement